Potential Adoption of IFRS by the United States: A Critical View - Kaya, Devrimi; Pillhofer, Julian A. (Accounting Horizons, 2013)
This paper discusses the potential adoption of International Financial Reporting Standards (IFRS) by the United States (U.S.). We use the reporting decisions of foreign U.S. listed firms as signals for U.S. capital markets' accounting standard preferences and demand for financial information. Our analysis of the 2009 (2010) annual reports filed with the SEC reveals that only 19 (23) percent of all foreign issuers file IFRS reports, although the reconciliation to U.S. GAAP requirement was eliminated in 2007. Thus, our results indicate that the majority of foreign filers in 2009 and 2010 use U.S. GAAP disclosure practices. Moreover, we provide evidence that cross-listed firms rarely change their filing behavior over the two-year sample period. Our analysis shows that the International Accounting Standards Board (IASB) is subject to problems connected with its structure and its limitations as a non-governmental organization (NGO). Therefore, we call for caution toward IFRS adoption by the SEC. We conclude by recommending an international treaty to provide better funding and oversight of the IASB and that steps are taken to harmonize enforcement of accounting standards around the world. Our analysis should be of interest to regulators, standard setters, national authorities, and companies interested in the current debate on a global set of accounting standard
WiSo-Import:2015-03-26:4738
Keywords: IFRS; US GAAP; SEC